Synthesis of ammonium persulfate microcapsule with a polyaniline shell and its controlled burst release. Issue 3 (6th August 2020) - Zhang, Qifan; Zuo, Mingming; Li, Guihao; Sha, Jianpeng; Zuo, Xiaobing
Abstract: Polymer hydraulic fracturing is important for increasing production during petroleum exploitation. After fracturing, the high‐viscosity polymer should be completely decomposed by gel breakers (ammonium persulfate [APS]) to realize high conductivity in the proppant pack. A new series of polyaniline microcapsules loaded with APS for the preparation of delayed‐release gel breakers were synthesized via in situ polymerization. The silica nanoparticles were doped in polyaniline to control the release of the encapsulated APS. The morphology, shell wall thickness, and elemental composition of the microcapsules were characterized by scanning electron microscopy, transmission electron microscopy, and two‐dimensional scanned energy‐dispersive X‐ray spectroscopy. The results revealed that the microcapsules were irregularly spherical with average diameters of about 5–6 μm and had shell thicknesses of 150–300 nm, and the silica nanoparticles had been successfully doped in the polyaniline shell. The microcapsules had a burst release pattern, and their initial release time was precisely controlled by adjusting the concentration and temperature of the sodium hydroxide solution. With increased demands for high performance delayed‐release microcapsules, the prepared polyaniline microcapsules loaded with APS show great potential for practical applications in petroleum exploitation, self‐healing coating, fiber printing, and grease. Abstract : Polyaniline microcapsules loaded with APS are prepared by in situ polymerization. Silica nanoparticles are embedded in the polyaniline shell to endow the microcapsules with the controlled release property. The microcapsules had a burst release pattern, and their initial release time is controllable in the sodium hydroxide solution.